Exploration of Learning Obstacle Based on Mathematical Understanding of Algebra in Junior High School - Muchamad Subali Noto; Surya Amami Pramuditya; Via Dwi Handayani (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
The difficulty of students related to algebra arises from the lack of students' mathematical understanding and Learning Obstacle (LO). One of the LO’s experienced by students is the epistemological obstacle in the form of the limited knowledge possessed by students in mathematical concepts related to algebraic form. The purpose of this study is to explore LO related to algebra material. This research method is qualitative with the consisted of 15 students of 7th grade. The results showed that the common students could not interpret concepts and clarify the elements of algebraic forms related to variables, coefficients and constants and students could not operate and simply algebraic forms. The teacher can make pedagogical and didactic anticipations to overcome the LO.